2022
DOI: 10.1111/mec.16718
|View full text |Cite
|
Sign up to set email alerts
|

Kleptoparasites of social spider colonies do not track hosts' subdivided population structure

Abstract: A negative correlation exists between dispersal ability and population differentiation, such that organisms with limited dispersal abilities would have genetically subdivided populations (Peterson & Denno, 1998) and greater inbreeding tolerance (Perrin & Mazalov, 1999;Waser et al., 1986). In the context of parasitism, dispersal should be associated with transmission across host individuals (Frank, 1996;Harbison et al., 2008): parasites leave the habitat provided by one host and establish in another host. A par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…The importance of geography is evident from the clear latitudinal cline in genetic variation in the PCA and the strong signal of IBD across all populations, as has been reported for other anadromous fishes (Hendry et al, 2004) as well as a wide range of taxa including mammals (e.g., Lucena‐Perez et al, 2020), invertebrates (e.g., Straus & Avilés, 2022), and plants (e.g., Twyford et al, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…The importance of geography is evident from the clear latitudinal cline in genetic variation in the PCA and the strong signal of IBD across all populations, as has been reported for other anadromous fishes (Hendry et al, 2004) as well as a wide range of taxa including mammals (e.g., Lucena‐Perez et al, 2020), invertebrates (e.g., Straus & Avilés, 2022), and plants (e.g., Twyford et al, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…We also had to replace kleptoparasites that were killed by the host when they could not escape an attack, as they would in a natural setting. Previous work in this system found that established female subadult and adult kleptoparasites remain within colonies to complete their life cycle, with dispersal likely involving juveniles and males (Cangialosi, 1990; see also Straus & Avilés, 2022). In these instances, we made every effort to ensure that the replacement kleptoparasite was of the same species and size as the previous one, although this was not always possible.…”
Section: Methodsmentioning
confidence: 99%